Development of Video Media Tutorials on Draping Techniques in Making Party Clothes - Mutiara Latifah Awe; Ernawati (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2026)
This research is motivated by the limited learning resources, as well as the difficulties of students in understanding and completing independent assignments related to draping techniques. This research aims to develop a video tutorial media for making party dresses using draping techniques in the Draping course in the Family Welfare Education Study Program, Bachelor of Fashion Design, Faculty of Tourism and Hospitality, Padang State University. The method used is the 4D development model (Define, Design, Develop, Disseminate), but the research was only carried out up to the Develop stage. The instruments used were a validity test questionnaire by media and material experts, and a practicality questionnaire by lecturers and students. The results of the validity test showed that the video media obtained a score of 92.85% (very valid category). The results of the practicality test showed a score of 83.06% by lecturers, 83.15% by a small group of students, and 82.26% by a large group of students, all in the very practical category. This learning video media is proven to be valid and practical as an alternative learning resource that supports the understanding of draping techniques in making party dresses.